Perception of TIC conflicts among secondary school students in a private school. School mediation as a response - José Luis González Sodis; Juan José Leiva Olivencia (Universidad de Málaga, 2022)
For some time now, there has been an increase in research on conflict in school contexts, which in turn broadens the field of conflict prevention in schools, suggesting proactive strategies for action. Therefore, the aim of this paper is to analyse how compulsory secondary education (ESO) students perceive one of the most latent conflicts of today, the violence produced with information and communication technologies (ICT). The research methodology used is quantitative with a non-experimental design based on a validated Likert questionnaire on the perception of school violence. The analyses carried out involved descriptive and inferential statistics. The population consisted of 220 ESO students from a private school in Malaga (Spain). The results indicate the existence of a significant level of ICT violence among students in the classroom and, to a lesser extent, student violence towards teachers, in both cases from the students' perspective. It is concluded that ICT violence among students and towards teachers can be addressed with the implementation of school peer mediation, a tool that is proposed as an appropriate formula for positive conflict management.